XV Symposium Internacional de Historia de la Masonería Española (Universidad de Lisboa, Lisboa, 2018): Semblanzas y conclusiones - Bubello, Juan Pablo (2018)
Between 11 and 13 October 2018, the XV International Symposium on the History of Spanish Masonry was held at the "Calouste Gulbenkian" Foundation (Lisbon, Portugal). Organized by the CEHME. as a continuation of the previous symposia that have been continuously carried out since 1983, brought together the most important specialists of the Old and New World as well as young researchers who are currently developing their postgraduate studies on various aspects of history of the masonry. In this work we display a general semblance of this academic event from its historical background and close with a series of conclusions.